Magnitude 2.8 Earthquake Caused by 90 Pounds (41 kg) Per Delay! Not So Fast - T. A. Davidsavor; J. Aiken; D. Rudenko; R. E. Burnham; J. K. Ratliff; I. G. Wong; C. T. Aimone-Martin (International Society of Explosives Engineers, 2023)
A small quarry blast was conducted with a maximum of 90 pounds per delay and shortly afterwards, area residents sensed ground motion and building shaking indicative of an earthquake. In addition, seismometers up to 500 miles (800 km) away recorded a magnitude 2.8 earthquake located in the area. Positioned in a seismically inactive area, southern Minnesota is not known for earthquakes. The earthquake was originally described by the USGS to be a surface blast at the quarry. Analysis showed that the earthquake occurred shortly (approximately seven seconds) after the quarry blast some distance away and well below the surface. This paper describes the evaluation of the “seismic events” including the blast, the following earthquake, initial governmental response, and provides the framework for assessing the relationship between the blast and the earthquake. The paper also discusses management of large volume claims from a complex event and presents a claims management strategy with best practices.